Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1371/journal.pone.0255785
|View full text |Cite
|
Sign up to set email alerts
|

What you say and what I hear—Investigating differences in the perception of the severity of psychological and physical violence in intimate partner relationships

Abstract: The correct communication of the severity of violence is essential in the context of legal trials, custody cases, support of victims, etc., for providing fair treatment. A narrator that communicates their experiences of interpersonal violence may rate the seriousness of the incident differently than a rater reading the narrator’s text, suggesting that there exist perceptual differences (PD) in severity ratings between the narrator and the rater. We propose that these perceptual differences may depend on whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
(49 reference statements)
1
9
0
Order By: Relevance
“…These results are consistent with those from a study that examined the justification of violence bidirectionally [ 32 ] and with more recent studies, which show higher levels of justification for physical violence committed by girls [ 33 ]. They are congruent with other reports [ 34 , 35 ] on the differences observed between boys and girls in their ratings of the severity of aggression, which suggests that participants may perceive that the same physical aggression is more harmful and has more serious consequences when the aggressor is a boy as well as when the victim is a girl [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 86%
“…These results are consistent with those from a study that examined the justification of violence bidirectionally [ 32 ] and with more recent studies, which show higher levels of justification for physical violence committed by girls [ 33 ]. They are congruent with other reports [ 34 , 35 ] on the differences observed between boys and girls in their ratings of the severity of aggression, which suggests that participants may perceive that the same physical aggression is more harmful and has more serious consequences when the aggressor is a boy as well as when the victim is a girl [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 86%
“…We studied the data set collected by Sikström et al [ 29 ], where accuracy and calibration biases were found for psychological and physical violence.…”
Section: Methodsmentioning
confidence: 99%
“…The data analyzed in this study [ 29 ] were collected in 2 phases (phase 1 [P1] and phase 2 [P2]) using the Prolific Academic website for online recruiting. The process used is described next.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations